Teaching critical thinking virtues and vices the case for Twelve Angry Men. - Hanscomb, S.
In the film and play Twelve Angry Men Juror 8 confronts the prejudices and poor reasoning of his fellow jurors, exhibiting an unwavering capacity not just to formulate and challenge arguments, but to be open-minded, stay calm, tolerate uncertainty, and negotiate in the face of considerable group pressures. In a perceptive and detailed portrayal of a group deliberation a ?wheel of virtue? is presented by the characters of Twelve Angry Men that allows for critical thinking virtues and vices to be analysed in context. This article makes the case for 1) the film being an exceptional teaching resource, and 2), drawing primarily on the ideas of Martha Nussbaum concerning contextualised detail, emotional engagement, and aesthetic distance, its educational value being intimately related to its being a work of fiction.
Keywords: Philosophy -- Periodicals; Teaching -- Periodicals